2014
DOI: 10.1016/j.str.2014.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Activation Route of the Schistosoma mansoni Cathepsin B1 Drug Target: Structural Map with a Glycosaminoglycan Switch

Abstract: Cathepsin B1 (SmCB1) is a digestive protease of the parasitic blood fluke Schistosoma mansoni and a drug target for the treatment of schistosomiasis, a disease that afflicts over 200 million people. SmCB1 is synthesized as an inactive zymogen in which the N-terminal propeptide blocks the active site. We investigated the activation of the zymogen by which the propeptide is proteolytically removed and its regulation by sulfated polysaccharides (SPs). We determined crystal structures of three molecular forms of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 46 publications
1
35
1
Order By: Relevance
“…As this motif occurs in all TrCB1 prosequences (Figure 2), sulfated polysaccharides facilitated auto-activation of both TrCB1.1 and TrCB1.4 (Figure 1). However, unlike in SmCB1 (Jílková et al, 2014), the products were relatively unstable at all tested pH values. Therefore, we did not use them in most subsequent experiments.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…As this motif occurs in all TrCB1 prosequences (Figure 2), sulfated polysaccharides facilitated auto-activation of both TrCB1.1 and TrCB1.4 (Figure 1). However, unlike in SmCB1 (Jílková et al, 2014), the products were relatively unstable at all tested pH values. Therefore, we did not use them in most subsequent experiments.…”
Section: Discussionmentioning
confidence: 71%
“…Auto-activation of recombinant cathepsin B1 from Schistosoma mansoni (SmCB1) is forced by negatively charged polysaccharides, such as sulfated glycosaminoglycans. Their binding to the SmCB1 pro-sequence destabilizes the pro-sequence/enzyme core junction (Jílková et al, 2014) and is mediated by a specific α-helix that contains a "heparin-binding motif "-XBBXBBX-(B is a basic amino acid and X refers to a hydropathic residue) (Horn et al, 2011;Jílková et al, 2014). A sequence alignment revealed that this motif is specific for trematode cathepsins B involved in the digestion of host proteins (Horn et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The resulting fragments were purified by RP-HPLC over a 5 mm C18 column (Luna, Phenomenex) equilibrated in 0.1% TFA and eluted with a linear gradient of 90% acetonitrile in 0.1% TFA. The purified peptides were characterized by ESI mass spectrometry on a Q-Tof Micro (Waters) (Jilkova et al, 2014).…”
Section: Declaration Of Interestsmentioning
confidence: 99%
“…The S. mansoni cathepsin B1 (SmCB1), which is a highly abundant digestive protease, was the focal point of various studies (reviewed in Ref. [104]). SmCB1 has been validated as a molecular target for therapy against schistosomiasis in a murine model of S. mansoni infection [105].…”
Section: Peptidasesmentioning
confidence: 99%